2015
DOI: 10.1248/bpb.b14-00410
|View full text |Cite
|
Sign up to set email alerts
|

ISG15 Regulates RANKL-Induced Osteoclastogenic Differentiation of RAW264 Cells

Abstract: Interferon-stimulated gene 15 kDa (ISG15) is a protein upregulated by interferon-β that negatively regulates osteoclastogenesis. We investigated the role of ISG15 in receptor activator of nuclear factor-κB ligand (RANKL)-induced osteoclastogenic differentiation of murine RAW264 cells. RANKL stimulation induced ISG15 expression in RAW264 cells at both the mRNA and protein levels. Overexpression of ISG15 in RAW264 cells resulted in suppression of cell fusion in RANKL-stimulated cells as well as the reduced expre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 28 publications
1
7
0
Order By: Relevance
“…The top two significantly enriched terms identified for upregulated proteins were regulation of actin cytoskeleton (hsa04810; p > 10 −4 ) and RHO GTPase effectors (R-HAS-195258; p > 10 −3 ) ( Figure 3 B), suggesting mechanisms by which SARS-CoV-2 remodels cytoskeletal networks for viral entry and budding. Additionally, three subsets of protein–protein interaction networks were identified, including several proteins involved in differentiation [ 42 , 43 , 44 , 45 , 46 ]. We identified significantly enriched terms in the group of downregulated proteins, including cellular hormone metabolic process (GO:0034754; p > 10 −5 ) and maintenance of gastrointestinal epithelium ( Figure 3 C).…”
Section: Resultsmentioning
confidence: 99%
“…The top two significantly enriched terms identified for upregulated proteins were regulation of actin cytoskeleton (hsa04810; p > 10 −4 ) and RHO GTPase effectors (R-HAS-195258; p > 10 −3 ) ( Figure 3 B), suggesting mechanisms by which SARS-CoV-2 remodels cytoskeletal networks for viral entry and budding. Additionally, three subsets of protein–protein interaction networks were identified, including several proteins involved in differentiation [ 42 , 43 , 44 , 45 , 46 ]. We identified significantly enriched terms in the group of downregulated proteins, including cellular hormone metabolic process (GO:0034754; p > 10 −5 ) and maintenance of gastrointestinal epithelium ( Figure 3 C).…”
Section: Resultsmentioning
confidence: 99%
“…In earlier studies, our group found an upregulation of IFNB , IFNG , and ISG15 in day 97 PI fetuses (21 days post maternal infection) [ 24 , 29 ]. These IFNs and ISG15 are known inhibitors of osteoclastogenesis, and their expression of these IFNs early in fetal development may not only inhibit ongoing osteoclastogenesis, but also cause the inhibition of osteoclastogenesis through hypermethylation of genes in most pathways affecting bone development and immune cell development [ 57 , 118 , 119 ]. By day 190 of gestation, Treg cells identified BVDV as self and suppressed the immune response to viral antigens; however, the epigenetic damage would have already been done.…”
Section: Discussionmentioning
confidence: 99%
“…IFN1-tunable immunomodulatory function in vivo can be related to their control of osteoclast formation [ 55 , 56 ] as well as lymphocyte development, maturation and memory cell retention [ 41 ], with both processes known to be strongly affected by age. In the present study, we observed a strong positive correlation between BM-MSC IL7 transcript expression, involved in both lymphocyte development and memory cells retention in the BM, and the expression of several ISGs.…”
Section: Discussionmentioning
confidence: 99%
“…As documented in previous independent studies, standard BM-MSC culture expansion leads to downregulation in the expression of a large number of genes, including ISGs [24,25,56]. To get insights into the in vivo IFN1 "status" of uncultured BM-MSCs, the IFN1 profile of purified CD45 low CD271 + cells was first compared to standard cultured BM-MSCs (nonstimulated, Figure 2).…”
Section: Ifn1 Profile Of Uncultured Cd45 Low Cd271 + Bm-mscs In Comparison To Cultured and Ifn1 Stimulated Bm-mscsmentioning
confidence: 94%